Nasobiliary drainage: an effective treatment for pruritus in cholestatic liver disease. Issue 5 (11th January 2022) - Ahmed, Wafaa; Jeyaraj, Rebecca; Reffitt, David; Devlin, John; Suddle, Abid; Hunt, John; Heneghan, Michael A; Harrison, Phillip; Joshi, Deepak
Abstract : Introduction: Nasobiliary drains (NBDs) have been successfully used to manage intrahepatic cholestasis, bile leaks and obstructive cholangitis. It allows external drainage of bile, bypassing the ileum where bile salts are reabsorbed. We assessed the utility of placement with effect on markers of cholestasis and patient symptoms. Methods: Consecutive patients undergoing NBD over 12 years for the management of pruritus were retrospectively analysed. Recorded variables included patient demographics, procedural characteristics and response to therapy. Results: Twenty-three patients (14, 61% male) underwent 30 episodes of NBD. The median age was 26 years old (range 2–67 years old). A single procedure was carried out in 20. One patient each had two, three and five episodes of NBD. The most common aetiologies were hereditary cholestatic disease (n=17, 74%) and drug-induced cholestasis (n=5, 22%), NBD remained in situ for a median of 8 days (range 1–45 days). Significant improvement in bilirubin was seen at 7 days post-NBD (p=0.0324), maintained at day 30 (335 μmol/L vs 302 µmol/L vs 167 µmol/L). There was symptomatic improvement in pruritus in 20 (67%, p=0.0494) episodes. One patient underwent NBD during the first trimester of pregnancy after medical therapy failure with a good symptomatic response. The catheters were well tolerated in 27 (90%) of cases. Mild pancreatitis occurred in 4 (13%) cases. Conclusion: NBD can be used to provide symptomatic improvement to patients with pruritus associated with cholestasis. It is well tolerated by patients. They can be used in pregnancy where medical management has failed.